Gov➔Value: How to combine reported quality experiences and patient-reported outcome measures. First results on vulvar cancer patients in an Italian Research Hospital - de Mattia, Egidio; Angioletti, Carmen; Perilli, Alessio; Guajardo Rios, Linda Stella; Garganese, Giorgia; Tagliaferri, Luca; Scambia, Giovanni; Fragomeni, Simona Maria; de Belvis, Antonio Giulio (Frontiers in Public Health, 2022)
Introduction Vulvar cancer (VC) accounts for <1% of cancers affecting the female gender. Clinical Pathways (CP) and Clinical Outcomes Monitoring are useful for providing high-quality care to these patients. However, it is essential to integrate them with the patient's perspective according to Value-Based Healthcare paradigms. Patient-reported outcome measures (PROMs) and patient-reported experience measures (PREMs) are tools for assessing outcomes and experiences with health care from the patient's perspective. The aim of this paper is to collect and synthesize PROMs and main stakeholders' experience on the VC CP, according to a value-based approach. Materials and methods To select the most appropriate instrument, a review was conducted on the main databases and official websites of specific institutions and organizations. In the second phase, a 2-round Delphi survey was conducted to assess the Reported Experience Measures (REMs) tool. Questions were evaluated according to four criteria (general relevance, evidence-based, measurability, actionability) and included if strong agreement was reached. A Principal Component Analysis (PCA) was executed. Cronbach's alpha and McDonald's omega were computed. Fisher's exact test and Wilcoxon rank sum test were used to compare ratings between groups. Descriptive statistics were performed for both PROMs and REMs instruments. Results For PROMs assessment, EORTC QLQ-C30 questionnaire was selected and administered to 28 patients. Global Health Status/Quality of Life and Functional Scales Scores were high or very high, while symptoms scale reported low or medium scores. The final REMs consists of 22 questions for professionals and 16 for patients and caregivers. It was administered to 22 patients, 11 caregivers, 5 physicians, 2 nurses and 1 clinical senior manager. PCA identified 4 components. Scale reliability was acceptable (α = 0.75 95% CI: 0.61–0.85; ω = 0.69; 95% CI: 0.54, 0.82). A statistically significant difference between the patient/caregiver group and the professionals was found for items 8 (follow-up), 10 (perceived quality), 12 (safety), and 16 (climate) (p = 0.02; p = 0.03; p < 0.001; p < 0.001, respectively). Discussion PROMs could provide new ways of intercepting patients' needs and feedback, thus acting on them. The proposed REMs tool would allow to detect information not available elsewhere, which, through Audit and feedback strategies, could lead to enhancement of healthcare experience, according to a value-based approach.